1998
DOI: 10.1007/s004310050820
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight at term impairs cord serum lipoprotein compositions and concentrations

Abstract: Intra-uterine growth retardation was accompanied by alterations in apolipoproteins and lipid compositions in the four lipoprotein fractions, which may impair lipid metabolism. Follow up studies on lipoprotein patterns in SGA infants are required to investigate whether such abnormalities at birth lead to diseases in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
6
17
1
Order By: Relevance
“…6,10,11 In agreement with our findings, Lane et al 5 found that preterm infants developing respiratory distress post-natally had significantly lower cord serum lipid levels than those of normal term infants or preterm infants free of respiratory distress. Significantly lower cord serum lipid levels are evidence of reduced essential fatty acids and long-chain polyunsaturated fatty acid supply, which could inhibit fetal growth in utero, delaying maturation of fetal lungs.…”
Section: Discussionsupporting
confidence: 91%
“…6,10,11 In agreement with our findings, Lane et al 5 found that preterm infants developing respiratory distress post-natally had significantly lower cord serum lipid levels than those of normal term infants or preterm infants free of respiratory distress. Significantly lower cord serum lipid levels are evidence of reduced essential fatty acids and long-chain polyunsaturated fatty acid supply, which could inhibit fetal growth in utero, delaying maturation of fetal lungs.…”
Section: Discussionsupporting
confidence: 91%
“…6,7,8 In agreement with our findings, Lane et al 5 found that preterm infants developing respiratory distress post-nataly had significantly lower cord serum lipid levels than those of normal term infants or preterm infants free of respiratory distress. Significantly lower cord serum lipid levels are evidence of reduced essential fatty acids and long-chain polyunsaturated fatty acid supply, which could inhibit fetal growth in utero delaying maturation of fetal lungs.…”
Section: Discussionsupporting
confidence: 82%
“…(4)(5)(6) and severe. (7)(8)(9)(10) Cord blood samples were obtained from umbilical vein immediately after delivery and allowed to clot at room temperature for 20 min. Serum was separated by centrifugation (20min, 2500 rpm) and kept at analysis was done.…”
Section: Methodsmentioning
confidence: 99%
“…But in the present study there was a lack of correlation between maternal post-delivery BMI and the neonates' lipid profile. Various factors during pregnancy are said to have strong influence on foetal lipid metabolism [12,13] and hence the scope of extensive research in the current field remains plausible.…”
Section: Discussionmentioning
confidence: 99%